Heat Capacities and Thermodynamic Properties of Pinnoite and Inderite - Hanyu Zheng; Kangrui Sun; Long Li; Yafei Guo; Tianlong Deng (Journal of Chemistry)
In this paper, in order to understand the thermodynamic properties of natural minerals of pinnoite (MgB2O4·3H2O, Pin) and inderite (Mg2B6O11·15H2O, Ind) deposited in salt lakes, heat capacities of two minerals were measured using a precision calorimeter at temperatures from 306.15 to 355.15 K after the high purity was synthesized. It was found that there are no phase transitions and thermal anomalies for the two minerals, and the molar heat capacities against temperature for Pin and Ind were fitted as Cp,m,pin = −2029.47058 + 16.94666T − 0.04396T2 + 3.89409×10−5T3 and Cp,m,Ind = −30814.43795 + 282.68108T − 0.85605T2 + 8.70708×10−4T 3, respectively. On the basis of molar heat capacities (Cp,m) of Pin and Ind, the thermodynamic functions of entropy, enthalpy, and Gibbs free energy at the temperature of 1 K interval for the two minerals were obtained for the first time.